Intramastoid solitary neurofibroma mimicking middle ear carcinoma. (12th December 2015) - Shi, Zhenshan; Zhuang, Qian; Cao, Dairong
We report an extremely rare case of intramastoid neurofibroma. A mass with destruction of the mastoid bone of a 51-year-old woman was examined with computed tomography. Subsequent magnetic resonance imaging demonstrated an ill-defined soft tissue mass with the opacification of mastoid air cells that had a mass effect in the same area. The patient underwent left subtotal temporal bone resection, and histological and immunohistochemical findings confirmed the lesion to be a neurofibroma. Given that similar imaging features of neurofibroma have been reported previously elsewhere in the head/neck and extremities, we suggest that it may be possible to include this tumor in the preoperative differential diagnosis.